Surface Photo Voltage Measurement Of Ultra-Violet Irradiation Effects In Oxidized Silicon Wafers - Kang, Ban Hong (2006)
The effect of cumulative ultraviolet (UV, 4.9eV) irradiation on the p-type silicon wafers, with thermal oxide between 3.3-20.0 nm, was investigated by using the surface photo voltage (SPV) technique. All the experiments were carried out in the silicon processing plant, Shin-Etsu Handotai (M) Sdn Bhd, which was located in the free trade zone, Ulu Klang, Selangor.